Penggunaan Aplikasi Blynk untuk Sistem Monitoring dan Kontrol Jarak Jauh pada Sistem Kompos Pintar berbasis IoT - Syukhron, Imam (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2021)
In the composting process, there are several aspects that need to be considered, namely temperature, humidity, pH content, and methane gas content in the compost. So that users can still monitor the condition of the compost during the composting process even though it is far from the compost location, this research provides an alternative solution to overcome this problem. The tool made in this study combines the capabilities of the Wemos D1 R1 as a data acquisition system equipped with a wifi module for sending data via the internet network, dht 22 sensor, pH sensor, and mq 4 sensor to determine the methane gas content in compost, and a special Android application blynk. as a monitoring aid. Wemos D1 R1 is also connected to a relay to regulate the ignition of a water pump or EM4 solution and two ac motors. Based on the tests conducted, it was found that each module can work properly according to its function and the results displayed in the Blynk application with the serial monitor are not much different and also at a distance of 25 m the device can still be controlled using the Blynk application even though there is a delay.